Paying participants in addiction research: Is cash king?. (3rd September 2017) - Neale, Joanne; Black, Lavinia; Getty, Mel; Hogan, Cassandra; Lennon, Paul; Lora, Cristina; McDonald, Rebecca; Strang, John; Tompkins, Charlotte; Usher, John; Villa, Gina; Wylie, Alan
ABSTRACT: I know there's some real scary, hardcore stories of people selling vouchers, but I've never experienced anything like that. If I got a voucher, I would often see it as a bonus. If it was for a shop I didn't use, I would sell it to someone I knew for the same amount of money – them just doing me a favour really. I wouldn't sell a voucher for less than its value.